Social documentary and new platforms for justice, symbolic reparations and empowerment. Case of Forced Sterilization in Huancabamba (2012 - 2016) - Ruiz, Inés (2019)
This article explains how the social documentary can function as a tool of denunciation and symbolic reparation as well as a vehicle for the empowerment of victims. Esperanza Huayama, vice president of the Asociación de Mujeres Afectadas por las Esterilizaciones Forzadas (AMAEF) and leader of the Asociación de Mujeres Campesinas de la Provincia de Huancabamba (AMBHA), is one of the most emblematic cases of forced sterilization in the province of Huancabamba, Peru. In the documentary Una voz estéril (2012), which I did as part of my doctoral research, Esperanza Huayama gives her testimony for the first time. Today she participates actively in protest marches in Lima and in meetings with parliamentarians, gives interviews to different public and independent media and interviews with the judges who have taken the case. She has travelled to Spain and England bringing the voice of the sterilized women of the country and feels responsible for representing them. She is aware of the impact this campaign has made on the media and the fact that she has become a public figure through the power of social networks and the denunciation documentary. Her case —and those of the women who make up the Instituto de Apoyo al Movimiento de las Mujeres (IAMAMC) and the AMBHA— provided me with evidence of how the case of sterilizations is remembered and how the citizens of Lima maintain a hegemonic and racist social discourse which allows them to ignore the rights of the populations affected by these policies.